FAR EASTERN CIVILIZATION AND LITERATURE OF THE EARLY MIDDLE AGES: THE WAY OF CHANGES - Shcherbakov, Yaroslav (Collection of scientific papers «ΛΌГOΣ», 2023)
Literature is as old as humanity itself. However, if we analyze the development of world literature, we will see that literatures that developed in different distant geographical regions at the same time have not only some distinctive but also many common features. Indeed, we can explain this fact by the globally world historical processes that affect the development of the civilization of the entire continent and the whole world. The mind of the enlightened author can feel global historical world processes. As a result, the mind of the enlightened author records them in the form of drama, poetry and prose.